Perioperative ketamine to reduce and prevent acute and chronic post-thoracotomy pain: a randomized, double-blind, placebo-controlled clinical trial - Ghezel-Ahmadi, Verena; Beck, Grietje; Bölükbas, Servet; Ghezel-Ahmadi, David (Journal of thoracic disease, 2024)
Perioperative ketamine to reduce and prevent acute and chronic post-thoracotomy pain: a randomized, double-blind, placebo-controlled clinical trial
Online veröffentlicht: 28. Dezember 2024
Gesehen am 08.04.2025